Strategy for the production of Citrus tristeza virus-free mandarin (Citrus reticulata) planting materials in the Darjeeling hills of India - B.K. JAYAKUMAR and K.B. PUN, K.K. BISWAS*, A. TARAFDAR, (Indian Phytopathology, 2009)
CTV-free mandarin (Citrus reticulata Blanco.) mother stocks were identified based on biological indexing, direct antigen coated enzyme-linked immuno-sorbent assay (DAC-ELISA) and reverse transcriptasepolymerase chain reaction (RT-PCR). Bud woods obtained from CTV-free mother stocks were grafted on Rangpur lime (C. limonia Osb.), rough lemon (C. jambhiri Lush.) and mandarin root stocks. The successful graft unions were maintained in insect-proof greenhouse and nurseries. Success of graft unions depended on the growing season but not on the citrus species used as the rootstock in the present study. Maximum number of graft unions were obtained in the month of March-April (60-82%) and August (60-65%). Three to four years old grafted mandarin plants were found to yield normal-sized fruits.